Increased ROS levels activate AMPK-ULK1-mediated mitophagy to promote pseudorabies virus replication - Yuan Zhao; Xiaoyi Qi; Zhenbang Zhu; Wenqiang Wang; Wei Wen; Xiangdong Li (Veterinary Research)
Abstract Increasing evidence has confirmed that oxidative stress plays a nonnegligible role in the viral pathogenic process. In this study, we investigated the role of reactive oxygen species (ROS) in the replication of pseudorabies virus (PRV). Our data showed that PRV infection initially enhanced the contact between the endoplasmic reticulum (ER) and mitochondria, leading to an upsurge of mitochondrial Ca2+ (mtCa2+) concentration, which resulted in the loss of mitochondrial membrane potential (MMP) and excessive ROS production. Instead of translocating it to the nucleus, PRV infection concurrently sequestered Nrf2 in cytoplasm impeding the efficient scavenging of intracellular ROS. The excessive ROS production and failure in ROS clearance contributed to the persistently high ROS levels during PRV infection. Furthermore, elevated ROS levels elicited activation of the AMPK-ULK1 axis, initiating PINK1-Parkin-dependent mitophagy that selectively degraded damaged mitochondria along with mitochondrial-localized mitochondrial antiviral signaling protein (MAVS). This process suppressed MAVS-mediated type I interferon responses by eliminating both dysfunctional mitochondria and their associated antiviral signaling platforms, thereby creating a cellular environment permissive to viral replication. Overall, our findings elucidated the mechanism by which ROS enables the virus to resist the host interferon immune response and provided a theoretical basis for ROS-based antiviral strategies.